The Effect Of Budget Transparency, Accountability And Human Resource Competence On The Management Of Village-Owned Enterprises In Pusako And Bungaraya District - Rosakinah Mawardah; Kartika Rachma; Rahmawaty hasibuan (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of budget transparency, accountability, and human resource competence on the management of Village-Owned Enterprises (BUMDes) in Pusako and Bungaraya Districts, Siak Regency. The study used a quantitative approach with a survey method on 34 respondents selected through purposive sampling. Data analysis was carried out using multiple linear regression with the help of SPSS. The results of the study showed that simultaneously budget transparency, accountability, and human resource competence had a significant effect on BUMDes management. Partially, only budget transparency had a positive and significant effect, while accountability and human resource competence had no significant effect. The Adjusted R Square value of 0.630 indicated that the three variables were able to explain 63% of the variation in BUMDes management, while the remaining 37% was influenced by other factors. It can be concluded that budget transparency is a factor that plays an important role in improving BUMDes management in Pusako and Bungaraya Districts, Siak Regency.